Enhanced oil palm waste properties through torrefaction and pelletization - Sambeth, Sharwin Kumar; Chandran, T. S. T.; Suriyati, Saleh; Noor Asma Fazli, Abdul Samad (IOP Publishing, 2021)
Torrefaction is a thermal pre-treatment process to treat biomass at temperature range of 200-300℃ under an inert atmosphere. It was known that torrefaction process strongly depended on the decomposition of the lignocellulosic constituents in oil palm waste namely hemicellulose, cellulose and lignin. The objective of this research is to study the effect of torrefaction on the characteristics of pellet formed from palm mesocarp fiber (PMF), oil palm frond (OPF) and palm kernel shell (PKS) as a solid fuel. The samples were torrefied at 270°C for 30 minutes. The torrefied samples were then densified into pellets through hot press machine at different temperatures (110 °C, 130 °C, 150 °C) and different pressure (10 MPa, 12 MPa, 14 MPa) for 20 minutes to find the optimum pelletization condition. The pellets were analyzed through mass yield, high heating value, fourier-transform infrared spectroscopy (FTIR) analysis, moisture absorption and compression test. Compression test is to study the strength of pellet by identifying the force required to break the pellet. The result shows that the mass yield of PKS was higher than PMF and OPF. The high heating value of torrefied oil palm waste improved as compared to the raw oil palm waste. Through FTIR, the changes of chemical bonds in oil palm waste after torrefaction have been identified. From the analysis of the pellet, the optimum conditions for pelletization were obtained, which are 130 °C and 12 MPa. The moisture absorption rate of torrefied pellet was lesser than raw pellets. Lastly, the torrefaction and pelletization process produced better quality pellets in term of high heating value, durability and more hydrophobic compared to raw pellets which can used as biofuel to replace the coal.